Improving patient safety: how and why incidences occur in nursing care - Maria Cecilia Toffoletto; Ximena Ramirez Ruiz (SciELO, 2013)
The present investigation was a cross-sectional, quantitative research study analyzing incidents associated with nursing care using a root-cause methodological analysis. The study was conducted in a public hospital intensive care unit (ICU) in Santiago de Chile and investigated 18 incidents related to nursing care that occurred from January to March of 2012. The sample was composed of six cases involving medications and the self-removal of therapeutic devices. The contributing factors were related to the tasks and technology, the professional work team, the patients, and the environment. The analysis confirmed that the cases presented with similar contributing factors, thereby indicating that the vulnerable aspects of the system are primarily responsible for the incidence occurrence. We conclude that root-cause analysis facilitates the identification of these vulnerable points. Proactive management in system-error prevention is made possible by recommendations.